Kindergarten Teachers' Use of Language ‎Communication Skills in E-Learning ‎Platforms - Al-Luhaybi ‎, Raniyah; Radwan, Azza (Jordan Journal of Educational Sciences, 2023)
The purpose of this study was to determine the extent to which kindergarten teachers use language communication skills when instructing students via online learning platforms. The quantitative descriptive method was utilized, and data were collected using a classroom observation form that includes four skills: listening, speaking, and learners' preparedness to read and write. The observation was carried out during online teaching using a kindergarten online platform in the first semester of 1443 AH.. The sample was randomly selected and consisted of 36 female teachers in public kindergartens in Al Baha City, Kingdom of Saudi Arabia. The results indicated that kindergarten teachers employed language communication skills at a medium level in all skills (listening, speaking, and learners' readiness to read and write). The results also demonstrated that there were statistically significant differences in relation to the educational qualifications in favor of teachers who hold bachelor's degrees. Furthermore, there were significant differences in writing readiness skills and in the total degree of language communication skills in favor of teachers who specialized in kindergarten. Finally, there were no significant differences that can be attributed to the differences in the years of teaching experience